Tooth Removal in the Leopard Gecko and the de novo Formation of Replacement Teeth - Brink, Kirstin S.; Henríquez, Joaquín Ignacio; Grieco, Theresa M.; Martin del Campo, Jesus Rodolfo; Fu, Katherine; Richman, Joy M. (Frontiers in Physiology, 2021)
Many reptiles are able to continuously replace their teeth through life, an ability attributed to the existence of epithelial stem cells. Tooth replacement occurs in a spatially and temporally regulated manner, suggesting the involvement of diffusible factors, potentially over long distances. Here, we locally disrupted tooth replacement in the leopard gecko and followed the recovery of the dentition. We looked at the effects on local patterning and functionally tested whether putative epithelial stem cells can give rise to multiple lineages in the enamel organs of new teeth. In adult animals, 2nd generation teeth with enamel and dentine were removed. The dental lamina was either left intact or disrupted in order to interfere with local patterning cues. The dentition was beginning to reform by one month and was nearly recovered by 2-3 months as shown in µCT scans and eruption of teeth labeled with fluorescent markers. Microscopic analysis showed that the dental lamina was fully healed by 1 month. The deepest parts of the dental lamina retained odontogenic identity as shown by PITX2 staining. A pulse chase was carried out to label cells that were stimulated to enter the cell cycle and then would carry BrdU forward into subsequence tooth generations. Initially we labeled 70-78% of PCNA cells with BrdU. After a 1-month chase, the percentage of BrdU+PCNA labeled cells in the dental lamina had dropped to 10%, consistent with the dilution of the label. There was also a population of single, BrdU- labeled cells present up to 2 months post surgery. These BrdU-labeled cells were almost entirely located in the dental lamina and were the likely progenitor/stem cells because they had not entered the cell cycle. In contrast fragmented BrdU were was seen in the PCNA-positive, proliferating enamel organs. Homoeostasis and recovery of the gecko dentition was therefore mediated by a stable population of epithelial stem cells in the dental lamina.